Disposal of green roofs: A contribution to identifying an "Allowed by legislation" end–of–life scenario and facilitating their environmental analysis. (December 2022) - Peri, Giorgia; Licciardi, Giada Rita; Matera, Nicoletta; Mazzeo, Domenico; Cirrincione, Laura; Scaccianoce, Gianluca
Abstract: The rapid and widespread deployment of green roofs requires the need to address their disposal and to assess the environmental impact of this phase of their life cycle to understand whether their current large-scale application may pose a problem. A review of the literature on green roofs environmental performance (particularly Life Cycle Assessment studies) has highlighted the lack of a standardized, commonly adopted, procedure for determining the treatments, recovery and/or disposal, to be assigned to waste from the removal of green roofs. In this regard, it should be mentioned that there is a lack of ad hoc legislation on the disposal of this technology (to the best of the authors' knowledge, even at the international level). In this paper, an attempt procedure is introduced to identify the end-of-life scenario of green roofs that does not conflict with the current regulations regarding wastes. Specifically, the procedure relies on an "attempt classification" of the waste from individual green roof elements and the priority criterion for intervention. This procedure might thus be used temporarily by technicians, pending the issuance of guidelines specifically dedicated to green roofs disposal, to model their end-of-life and thus assess the environmental impact of this phase of the life cycle. The feasibility of this proposal was verified through a field application. Besides the methodological proposal, the results of the work indicated the need to review the current waste legislation and update it -at least the Italian one - to also consider new materials used in green transition technologies. Highlights: Disposal of green roofs (GRs) is an open topic, as it has not yet been codified. An attempt procedure is introduced to identify a tentative GR end-of-life scenario. An "attempt" waste classification of the elements of the case study is delivered. Drain and filter need analytic characterization even for an attempt classification. Legislation requires updates to consider new waste from the ecological transition.